Evidence for sea level and monsoonally driven variations in terrigenous input to the northern East China Sea during the last 24.3 ka. (9th June 2015) - Chang, Fengming; Li, Tiegang; Xiong, Zhifang; Xu, Zhaokai
Abstract: Geochemical and sedimentological analyses of core PC‐1 recovered from the northern East China Sea (ECS) provide insights into variations in terrigenous input associated with sea level and climate changes over the past 24.3 ka. Based on high‐resolution multiproxy records, our results suggest that the competing processes of sea level and monsoonally driven precipitation determined terrigenous input to the northern ECS. Dominance of terrigenous material, along with relatively light Globigerinoides ruber δ 18 O, indicates that the Last Glacial Maximum (LGM) lowstand of sea level has occurred during the period 21.5–19.6 ka, not suggesting an early slow rise but supporting the conventional LGM age of 21 ka. This LGM lowstand was terminated by the rapid sea level rise of 19 ka meltwater pulse (MWP), which is well expressed by the nearly synchronous decreases in both terrigenous detritus and mean grain size from 19.6 to 18.9 ka. MWP‐1A is clearly marked in our records by a sharp reduction in terrigenous input and pronounced maxima of G. ruber δ 18 O at 15.3–14.8 ka, given the considerable age uncertainties of deglacial marine radiocarbon samples. A slightly increasing input of terrigenous matter is noted after 13.4 ka, potentially pointing to a sea level fall following the Inter‐Allerød Cooling Period, which was seldom reported previously. Although MWP‐1B did not leave robust signatures in terrigenous input, it is explicitly captured by the heavy δ 18 O of G. ruber and decline in mean grain size at 11.5–10.9 ka. MWP‐1c probably occurred in a broad millennial interval with multiple peaks, which are robustly marked by the abrupt variations in terrigenous input and marine organic matter at 9.7–9.3 and 9.1 ka, respectively. During the late Holocene, the effect of continuously weakening monsoon precipitation overwhelmed that of stable sea level resulting in a uniform increase in the proportion of marine‐derived organic matter after 5.5 ka. Key Points: Supporting evidence for the conventional LGM lowstand age of 21 ka Clear geochemical and sedimentological signatures of meltwater pulses Potentially sea level fall following the inter‐Allerød cold interval